PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM DENGAN INFLASI SEBAGAI VARIABEL MODERASI : (studi pada Perusahaan Manufaktur Barang Dan Konsumsi Yang Terdaftar Di Bursa Efek Indonesia 2019-2021) - Nur Ani, Heti; Indira, Irma; Rodhiyah, Ma’rufatur; Dedyansyah, Achmad Farid (STIE Mahardhika, 2024)
The aim of this research is to analyze and test whether there is an influence of company size and profitability on stock returns with moderation proxied by inflation. Quantitative methods were used in this research. Manufacturing companies in the goods and consumption sectors were used as the population in the research, the data of which was obtained from the 2019-202 BEI. In collecting samples, this research used criteria in determining the sample so that 54 samples were obtained based on the specified criteria. This research data was analyzed using MRA analysis version 26 with SPSS tools. The results of the research prove that profitability has no effect on stock returns, stock returns are able to influence inflation and company size, inflation is able to strengthen the influence of company size and profitability on stock returns.